Clinical and Phenomenological Characteristics of Patients with Task-Specific Lingual Dystonia: Possible Association with Occupation - Yoshida, Kazuya (Frontiers in Neurology, 2017)
Background: Lingual dystonia is a subtype of oromandibular dystonia, which is a movement disorder characterized by involuntary sustained or intermittent contraction of the masticatory and/or tongue muscles. Lingual dystonia interferes with important daily activities such as speaking, chewing, and swallowing, resulting in vocational and social disability. Objective: The aim of this study was to investigate a possible relationship between occupation and the development of lingual dystonia. Methods: Phenomenological and clinical characteristics of 95 patients [53 females (55.8%) and 42 males (44.2%), mean age 48.0 years] with task-specific, speech-induced lingual dystonia were analyzed. Structured interviews were carried out to obtain information regarding primary occupation, including overtime work and stress during work. The factors that might have influenced the development of lingual dystonia were estimated using multivariate logistic regression analysis of the 95 patients with lingual dystonia and 95 controls [68 females (71.6%) and 27 males (28.4%), mean age 47 years] with temporomandibular disorders. Results: Overall, 84.2% of the patients had regular occupations; 73.8% of the patients with regular occupations reported working overtime more than twice a week, and 63.8% of them experienced stress at the workplace. Furthermore, 82.1% of the patients had engaged in occupations that required them to talk to customers or other people under stressful situations over prolonged periods of time for many years (mean: 15.6 years). The most common occupation was sales representative (17.9%), followed by telephone operator (13.7%), customer service representative (10.5%), health care worker (9.5%), waiter or waitress (5.3%), receptionist (5.3%), and cashier (5.3%). Twenty-nine patients (30.5%) had tardive lingual dystonia. Logistic regression analyses revealed that frequent requirements for professional speaking (p=0.011, odds ratio: 5.66), high stress during work (p=0.043, odds ratio: 5.4), and neuroleptic use (p=0.032, odds ratio: 2.52) were significant contributors to the manifestation of lingual dystonia. Conclusion: Professions in which conversations in stressful situations are unavoidable may trigger lingual dystonia. Therefore, speech-induced lingual dystonia can be regarded as occupational dystonia in certain cases.